Modelling non-alcoholic fatty liver disease using patient derived liver stem cells and hepatic organoids - Lim, Yee Siang (Nanyang Technological University, 2020)
Non-alcoholic fatty liver disease (NAFLD) is described as a global epidemic. With no approved drugs in the market, the disease imposes huge economic and healthcare burden to the society. In-vitro models are deemed as a potential method to test and screen drugs. Hepatic organoids (HOs) differentiated from adult stem cells derived from the liver are attractive in-vitro models due to its ability to recapitulate functions of the liver. In-vitro models were established using tissues from Non-alcoholic steatohepatitis (NASH) patients and healthy donors. A transcriptomics approach was taken to determine if HOs from NASH donors can better recapitulate the disease in-vitro. It was discovered that NASH HOs have increased expression of genes associated to NASH. Inducing steatosis resulted in distinct upregulation of genes in NASH HOs which are associated to worse outcome in NAFLD patients. Together, the analysis suggests that HOs from NASH donors are better in-vitro models to recapitulate NAFLD.